Effects of Climate Change Policies on Insurance Industry Stability - Muchomba, Julius (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to investigate effects of climate change policies on insurance industry stability Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study's findings revealed significant insights. Empirical studies demonstrated that climate change policies influenced insurance industry practices, prompting insurers to adopt climate-resilient strategies. It was observed that insurers, aligning with these policies, modified their risk assessment methodologies to incorporate climate-related risks. The studies further highlighted that policy-induced changes motivated insurers to innovate and offer climate-specific insurance products, addressing the emerging needs of policyholders. Overall, the research underscored the importance of effective collaboration between policymakers and insurers to enhance industry stability in the face of climate-related challenges. Unique Contribution to Theory, Practice and Policy: Institutional Theory, Risk Management and Stakeholder Theory may be used to anchor future studies on Effects of Climate Change Policies on Insurance Industry Stability. Stakeholders should proactively engage with policymakers and collaborate on designing climate change policies that foster stability within the industry. Governments and regulatory bodies should adopt a multi-faceted approach to ensure insurance industry stability amid climate change.